The Role of Green Human Resource Management in Strengthening Corporate Governance for Environmental Sustainability - Mercado , Jillard O.; Odoya, Marge Ethan U.; Mercado , Rozette (International Review of Management and Marketing, 2026)
The study investigates how Green Human Resource Management practices impact environmental results at rural banks located in the Northern part of Surigao del Sur in the Philippines. The researchers used a quantitative research design to gather information about 111 employees who worked at six rural banks. The researchers used descriptive statistics with Analysis of Variance and regression analysis to examine their data. The study found that organizations maintain a high frequency of GHRM practice execution which results in superior environmental outcomes, because the practices create 43.7 percent of environmental performance variance through their implementation with a specific positive effect size of β = 0.661 at p < 0.001. The implementation of green training and development showed the highest level of execution, while green pay, reward, and recognition received the lowest implementation score (M = 3.66) because organizations only implemented incentive-based systems at a minimal level. Employee environmental knowledge emerged as a critical factor that determines the degree of GHRM implementation. The research demonstrates that organizations need to establish structural GHRM practices, but their success in sustainability projects depends on their ability to synchronize performance assessment methods with reward distribution practices. The study provides developing economy evidence from rural banks which helps explain the implementation of GHRM practices, while suggesting methods to improve sustainability-oriented human resource practices.